Distribution maps of the outdoor myrmicid ants (Hymenoptera, Formicidae) of Finland, with notes on their taxonomy and ecology - Saaristo, Michael (Entomologica Fennica, 1995)
Twentytwo species of myrmicid ants maintaining outdoor populations are listed for Finland. Four of them, Myrmica hellenica Forel, Myrmica microrubra Seifert, Leptothorax interruptus (Schenck), and Leptothorax kutteri Buschinger are new to Finland. Myrmica lonae Finzi is considered as a good sister species of Myrmica sabuleti Meinert, under which name the species has earlier been known in Finland. Myrmica specioides Bondroit is deleted from the list as no samples of this species could be located in the collections. The distribution of each species in Finland is presented on 10 x 10 km square grid maps. The ecology of the various species is discussed. Also some taxonomic problems are dealt with.